(untitled) (Innovaciones Educativas, 2021)
In recent years, pedagogical models of the highest level have shown a great expansion towards blended learning (Ibáñez, de Benito Crosetti, Garcías, and Cervera, 2018; Mariño, 2007; Morán, 2012; Vera, 2008). These models allow for incorporating both the face-to-face and virtual environments in such a way that it allows the optimization of the most compelling qualities of each of them. Among the different ways of implementing blended learning is the flipped classroom (Coufal, 2014; Schneider, Suhr, Rolon, & Almeida, 2013), which has been continuously acquiring more relevance. In these contexts, teachers face the transformation of all their practices; among them, evaluation is a relevant axis that has been little addressed. Based on this problem, the research presented in this work addressed the evaluation carried out in three school subjects. The approach, strategies, and instruments were examined that one may establish the particularities of evaluation in these contexts. Through a qualitative approach, information was collected through interviews, observations, and documentary analysis. Likewise, a constant comparative method was adopted, and the categories that allowed characterizing evaluation in flipped classroom contexts we reconstructed. The decisions and actions regarding evaluation demonstrated how the pedagogical proposal and the didactic possibilities of the activities define the evaluation’s characteristics more than it does the qualities of the technological tools.